Exploring the planning challenges of service delivery in local municipalities: the case of the Midvaal local municipality - Ndlovu, Nokwenama Sihawukele Mzuzu (My University, 2016)
At the birth of the democracy, there were countless hopes, promises and desires that came with the new era. Many South Africans had a renewed hope for improved living conditions and economic opportunities. The new hope and desires are well articulated in the African National Congress 1994 election slogan ‘a better life for all’. Provision of housing was amongst the list of promised goods. While many South Africans have received the houses they were promised, millions still reside in poor living conditions, crammed in shacks and squatter camps. Other communities have felt the brutal hand of the government, and have been uprooted from their homes to make way for new developments. The ferocious acts have not gone unnoticed by the affected communities as they have taken on the streets as a platform to demand for basic services to be delivered in their locations. In recent years, service delivery related protests have become the order of the day where communities are disregarding the current channels of engagement in favour of new insurgent practices. The new platforms of engagement create a labyrinth of complex situations that planners have to muddle through. With the mounting public protests and increasing demands for basic services, planners are inescapably knotted in complex situations that require immediate response. Planning in diverse and multi-cultural contexts is challenging as planners are confronted with a web of contextual, administrative and political issues. It is from this premise that the study explored the planning challenges of service delivery in local municipalities. The challenges were probed through exploring the planning challenges of delivering housing in local municipalities. From the discussions in the report and the chosen case study of Sicelo Shiceka informal settlement in Midvaal Local Municipality it was evident that there were complexities encountered when it came to delivering services in a context entangled in complex party politics. Issues of power, politics, limited capacity, multiple stakeholders, unrealistic demands and the multi-cultural contexts are just some of the few challenges planners stumble across. From the study, it was evident that the South African rhetoric on service delivery makes it difficult to deliver houses in such contexts as people feel entitled to the services but have no responsibility to the services. The study highlights the difficulty of planning within a maturing democracy. The research further suggests that planning is influenced by politics even when it comes from an objective approach.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Development Planning
Keywords: Municipal services--South Africa; Local governments--South Africa